Epigenetic therapy: azacytidine and decitabine in acute myeloid leukemia. Issue 5 (4th May 2018) - Bohl, Stephan R.; Bullinger, Lars; Rücker, Frank G.
ABSTRACT: Introduction : The majority of patients with acute myeloid leukemia (AML) are older and exhibit a poor prognosis even after intensive therapy. Inducing differentiation and apoptosis of leukemic blasts by DNA-hypomethylating agents, like e.g. azacytidine (AZA) and decitabine (DAC), represent well-tolerated alternative treatment approaches. Both agents show convincing response as single agents in AML. However, there is a lack of knowledge regarding molecular mechanisms and predictive biomarkers for these agents. Areas covered : This review will (i) provide an overview of the current knowledge of molecular mechanisms underlying the action of these drugs, (ii) report promising predictive biomarkers, (iii) elude on new combined treatment options, and (iv) discuss novel approaches to improve outcomes. A literature search was performed using PubMed to find recent major publications, which provide biological and clinical research about epigenetic therapy in AML patients. Expert commentary : Numerous studies have demonstrated that HMA therapy with AZA or DAC may lead to significant response rates, even in pre-treated patients. Nevertheless, there is still an unmet need to further improve outcome in elderly AML patients. Therefore, novel treatment combinations are needed and some of them, such as AZA plus venetoclax, already show promising results.